2011
DOI: 10.1111/j.1399-3038.2011.01192.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of asthma in genetically susceptible children: A multifaceted intervention trial focussed on feasibility in general practice

Abstract: Other primary preventive asthma-reducing interventions were shown to be effective in reducing the occurrence of asthma for at least the first 7-8 yr of life. The multifaceted PREVASC allergic asthma primary preventive intervention was effective in reducing the exposure to inhalant and food allergens, but was not feasible for the parents. A lack of sufficient room for improvement focus on stimulating adherence seemed to be involved. It is suggested that a multifaceted environmental exposure-reducing interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…The Canadian Childhood Asthma Primary Prevention Study at their 7-year follow-up found a significant reduction in the prevalence of asthma in the intervention group compared with their control group (14.9% vs 23%) 26. The requirement for the combination of dietary modification in addition to house dust mite avoidance and the additional need for prolonged breast feeding/delayed introduction of allergens into the infants' diet may account for the lack of success of single-intervention trials of house dust mite avoidance,27 28 or dietary modification,29 to significantly reduce the prevalence of asthma. Manchester Asthma and Allergy Study is the epitome of single-allergen intervention where extensive mite allergen-avoidance measures resulted in reducing HDM levels to very low levels, and yet, failed to prevent asthma 30.…”
Section: Discussionmentioning
confidence: 99%
“…The Canadian Childhood Asthma Primary Prevention Study at their 7-year follow-up found a significant reduction in the prevalence of asthma in the intervention group compared with their control group (14.9% vs 23%) 26. The requirement for the combination of dietary modification in addition to house dust mite avoidance and the additional need for prolonged breast feeding/delayed introduction of allergens into the infants' diet may account for the lack of success of single-intervention trials of house dust mite avoidance,27 28 or dietary modification,29 to significantly reduce the prevalence of asthma. Manchester Asthma and Allergy Study is the epitome of single-allergen intervention where extensive mite allergen-avoidance measures resulted in reducing HDM levels to very low levels, and yet, failed to prevent asthma 30.…”
Section: Discussionmentioning
confidence: 99%
“…Various publications have reported the beneficial effects of such efforts on hospitalisation rates and emergency department visits, and on the prevalence of asthma during childhood [55,56]. Stopping women from smoking before or during pregnancy remains a challenge, however, as illustrated by the conflicting outcomes of intervention studies [55,57,58]. A randomised controlled trial (RCT) comparing nicotine patches with placebo in pregnant smokers showed no significant effects on mothers' smoking rate or reported respiratory symptoms in their offspring at 2 years of age [57].…”
Section: Second-hand Smoke Exposurementioning
confidence: 99%
“…Seventy-five full-text articles were read. Forty-five studies were excluded for the following reasons: no relevant outcomes, 18 studies [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] ; the trial did not include a control group, 7 studies 56-62 ; the interventions were not aimed at parents of young children, 3 studies [63][64][65] ; the reporting period was ,1 month, 2 studies 66,67 ; data necessary for analysis were missing, 10 studies [68][69][70][71][72][73][74][75][76][77] ; the paper was a review article, 1 study 78 ; the article was a protocol, 2 studies 79,80 ; the article was a follow-up of a previous study, 1 study 81 ; there was no true control group (eg, 2 active interventions were compared), 1 study 82 .Thirty studies met the inclusion criteria for this review. [20][21][22][23][24][25][26][27][28][29][30][31]…”
mentioning
confidence: 99%